Complying with consumer law: framework and advice. (2nd April 2019) - Burrows, Claire; Booth, Mark
Abstract : The Competition and Markets Authority (CMA) has recently put its focus on the care home sector, since it has emerged that care homes do not always comply with consumer law. Claire Burrows and Mark Booth discuss the advice it has published.